The impact of genetic variants in IL1R2 on cervical cancer risk among Uygur females from China: A case–control study. Issue 1 (20th November 2018) - Niu, Fanglin; Wang, Tianchang; Li, Jing; Yan, Mengdan; Li, Dianzhen; Li, Bin; Jin, Tianbo
Abstract: Background: Disordered inflammation and immune response is an acknowledged risk factor for cervical cancer development. Interleukin‐1 receptor type 2 (IL1R2) is a decoy receptor for IL‐1 cytokines and involved in host inflammatory and immune progression which could lead to the lesion and neoplasia of cervix. In this study, we aimed to evaluate the relationships between IL1R2 polymorphisms and cervical cancer risk in Uygur females from China. Methods: In this case–control study, genotypes of six selected variants (rs11674595, rs4851527, rs719250, rs3218896, rs3218977, and rs2072472) distributed in IL1R2 were detected among 247 cervical cancer patients and 286 healthy controls with the usage of an Agena MassARRY method. Furthermore, Genetic models and haplotype analyses were conducted to estimate the associations of IL1R2 polymorphisms with cervical cancer risk. Results: After statistical analyses, rs719250 (odd ratio [OR] = 1.436, 95% confidence interval [95% CI] = 1.079–1.911, p = 0.013) and rs3218896 (OR = 1.552, 95% CI = 1.080–2.229, p = 0.017) showed obvious evidence in correlation to cervical cancer susceptibility owing to the surviving significant differences between cases and controls in allele model. Genetic model analyses also revealed significant associations of rs719250 and rs3218896 with cervical cancer risk in the codominant model, the dominant model and the log‐additive model even after adjustment for age ( p < 0.05). Moreover, haplotype "T/A" of rs11674595/rs4851527 (adjusted OR = 0.73, 95% CI = 0.54–0.98, p = 0.037) and "T/C" of rs719250/rs3218896 (adjusted OR = 1.61, 95% CI = 1.10–2.36, p = 0.015) exhibited protective and risky effects for Uygur individuals on cervical cancer development, respectively. Conclusion: Our data first shed the new light on the associations of IL1R2 polymorphisms with cervical cancer susceptibility among Uygur females. These results are supposed to facilitate the tumorigenesis genetic research among Chinese minorities. Abstract : Interleukin‐1 receptor type 2 (IL1R2) is involved in the inflammatory responses and contributes to cervical cancer development. This study showed evidence for IL1R2 polymorphisms in correlation to cervical cancer risk in Uygur females. Our research could provide bases for tumorigenesis genetic research in Chinese minorities.